TURNOVER INTENTION KARYAWAN: SAAT BEBAN KERJA DAN KONFLIK MENJADI FAKTOR PENENTU [EMPLOYEE TURNOVER INTENTION: WHEN WORKLOAD AND CONFLICT BECOME DETERMINING FACTORS] - Sutoro, Moh; Solihin, Dede (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze the effect of workload and work conflict on employee turnover intention at PT Pratama Abadi Industri in Tangerang. Using a quantitative associative approach, the study involved 75 employees in the assembling department. Data were collected through observation, questionnaires, and literature review, and analyzed using multiple linear regression. The results indicate that both workload and work conflict positively affect turnover intention, meaning that high work pressure and interpersonal conflicts increase employees’ intention to leave the organization. Simultaneously, these factors have a stronger impact, highlighting the importance of managing workload effectively and resolving conflicts to create a healthy and supportive work environment. The findings emphasize the need for companies to maintain employee satisfaction, motivation, and retention to ensure organizational sustainability.